Are wading birds the ideal focal species for broader bird conservation? A cost-effective approach to ecological network planning - Yuting Xie; Jie Zou; Yanzhuo Chen; Fang Li; Qianzi Jiang (Ecological Indicators, 2024)
Focal species play a crucial role in planning ecological networks (ENs). Despite the finding that ENs designed for a specific focal species can yield benefits for associated communities, current practices of applying individual focal species have faced criticism for oversimplifying intricate ecosystems. Besides, the aggregation of ENs for individual species has been demonstrated as ineffective and costly. To improve cost-effectiveness, species with similar habitat preferences are typically conserved using shared strategies. Thus, drawing from the habitat preference of wading birds for blue and green spaces, we hypothesized that an EN for wading birds may benefit co-existing water and forest birds that prefer blue or green spaces. To validate this hypothesis, we conducted our study in the Yangtze River Delta’s Ecological Green Integration Demonstration Zone. We simulated six scenarios S1-S6 to compare the cost-effectiveness of focal species networks, respectively for water, forest, and wading birds in the S2-S4, with the aggregate networks in the S5-S6. During ENs’ construction, we employed the InVEST Habitat Quality model, MSPA, MCR model, and Linkage Mapper Tools. Furthermore, we selected the most cost-effective EN by calculating six ENs’ connectivity-cost ratio (CCr index) and ranked the conservation priority for its sources and corridors. The results showed that the EN4 ranked highest in the CCr index and displayed a high conservation efficiency for all bird species. 93.41% of primary ES4 and 42.46% of secondary ES4 overlapped with the ecological conservation redline and the permanent basic farmland and could be well protected under current statutory planning. Our findings confirm that wading birds are the ideal focal species in EN planning for broader bird conservation in the context of the Yangtze River Delta. The constructed regional EN could contribute to establishing a linkage with the supra-regional EN and the world’s major bird migration flyway. Moreover, our cost-effective approach to bird conservation could provide new insights for targeting focal species from the perspective of habitat preference in multi-species EN planning.